KAJIAN HISTOKIMIA SEBARAN KARBOHIDRAT ASAM PADA LAMBUNG DEPAN SAPI SUMBA ONGOLE (Bos indicus) - Paulino, Theresia Bergita; Amalo, Filphin Adolfin; Maha, Inggrid Trinidad (JURNAL KAJIAN VETERINER, 2020)
Sumba ongole (Bos indicus) is one of the Indonesian local cattle breeds that has a high number of carcasses and good adaptability to the dry climate and low humidity on the island of Sumba. Cattle have a forestomach consisting of the rumen, reticulum, and omasum, which functions to ferment and absorb nutrition. This study aims to determine the distribution of acid carbohydrates in the rumen, reticulum, and omasum of sumba ongole cattle. Six samples of the rumen, reticulum, and omasum were collected from East Sumba Slaughter House, fixed in formalin 10 %, processed histologically, and continued with alcian blue (AB) staining. The result showed the various/different intensity of acid carbohydrates in each of the tunica of the rumen, reticulum, and omasum. The distribution is mostly found in the stratum corneum lamina epithelium. The results of this study indicate that the stratum corneum is the layer that is more frequently exposed to food that requires acid carbohydrates in its function to protect the forestomach as well as to lubricate the food to make it easier to digest.